Cold chain logistics: the pathways of vaccines and thermolabile medicines to patients in municipal primary care - Ferman, Patricia Maria Flores; Gonçalves, Regina Aparecida Correia; Oliveira, Arildo José Braz de (Acta Scientiarum. Health Sciences, 2024)
For the quality assurance of thermolabile medicines and vaccines, it is imperative that all stages of the cold chain are satisfied. The aim of this study was to analyze the temperature of boxes containing medications and vaccines on routes between the Regional Health Facility of Apucarana, Paraná State, to the cities it serves, using the parameters of the Cold Network Manual. The temperature within the boxes remained within the recommended range (2 to 8°C) for 44.44% of the routes that were tracked, of which 30.55% had boxes assembled with medications and 13.88% had boxes containing vaccines. Therefore, for most of the routes (55.55%), the internal temperature of the boxes was outside the recommended range, i.e., below 2°C or above 8°C. It was concluded that the transport of thermolabile drugs and vaccines between the Regional and Municipal levels do not meet the technical specifications provided for in the Cold Network Manual. As the temperature within the boxes exceeded the recommended temperature range for more than half of the routes followed, it can be inferred that the processes related to the transport of these products are not being followed with the necessary rigor. Municipal managers should be aware of these needs including the modernization of measurement instruments and equipment and the investments in continued education for the team that operates the cold chain network.